Growth Mindset and Grit: Examining the Academic Buoyancy of College Students Implementing Online Lectures - Pratiwi, Marisya; Iswari, Rosada Dwi; Nesvita, Melania Delaritas; Khairiyah, Ummul Sabila (Universitas Negeri Malang, 2023)
One of the consequences felt by the world of education from the outbreak of the Coronavirus is that higher education institutions are required to apply online learning methods. Online learning itself has strengths, challenges, and obstacles in its implementation. Therefore, students need the ability to overcome the obstacles and challenges that are felt in the daily online learning process, namely academy buoyancy. This research seeks to find the role of the growth mindset and grit in academic buoyancy in college students who face online lectures. This research involved 140 students who were in their first year when this research was conducted (class of 2021). The results of hypothesis testing using multiple regression analysis showed an F value equal to 19.597 with a p-value equal to 0.000 (p less than 0.5). These results indicate that the hypothesis in this study is accepted, that the growth mindset and grit have a role in academic buoyancy among students who are studying online. The results of further calculations show that the role of the growth mindset and grit on academic buoyancy is 22.2 percent (R2 equals 0.222).